THE BUDDHIST CONCEPTION OF OMNISCIENCE - PANDEY, LAKSHUMAN (My University, 1972)
As its central purpose, the thesis outlines the Buddhist conception of human omniscience as developed by the philosophers of later Vijnanavada Buddhism, i.e., DharmakIrti, Prajnakaragupta Santarakita and Kamalasila. It attempts to show how those philosophers dialectically established the possibility of human omniscience and the omniscience of the Buddha. The concept of human omniscience was introduced into Indian philosophy because of the religious controversies between Heterodox (Nastika) schools, such as Jainism and Buddhism, and Orthodox (Astika) schools, especially Nyaya-Vaiseika, Sankhya-Yoga, Mimamsa and Vedanta. The Mimamsakas began the argument with claims for the omniscience of the Vedas; the Naiyayikas followed with the attribution of omniscience to God. When the Buddhists, in turn, maintained the omniscience of the Buddha, the Mimamsakas raised objections to the concept of human omniscience, the omniscience of the Buddha, of God, and of any human religious teacher. In order to refute these objections and to assert once again the superiority of the Buddha and his teachings of Dharma, the later Buddhist philosophers sought to dialectically established the concept of human omniscience. The Buddhist argument was the product of constant interaction and debate with other Indian religious and philosophical schools, and it is clear that omniscience was and continues to be one of the pivotal topics for all schools of Indian philosophy. The Buddhists have used logical arguments to support the concept of human omniscience. They have established the omniscience of the Buddha using the logical methods of presumption and inference. They have provided the answers from the Buddhist point of view to the Mimamsakas' objections against the concepts of human omniscience and the omniscience of the Buddha. The Buddhists maintain that an omniscient person perceives all objects of the world simultaneously in a single cognitive moment. They have also argued that only an omniscient person can teach Dharma. The aim of the Buddhists was to prove the superiority of Buddhism among all religions, because it is based on the teachings of an omniscient being. In brief, this thesis outlines the development of the concept of omniscience, which the Buddhists hold to be the necessary and sufficient condition for perception of supersensuous truths such as Dhatma.
Keywords: History of Religions of Eastern Origins; History of Religions of Eastern Origins